Exploratory agent-based model to understand migration scenarios: a study from the Indian Himalayan Region, Uttarakhand. Issue 1 (2nd January 2021) - Sharma, Divya; Khandekar, Neha; Sachdeva, Kamna
ABSTRACT: Migration is a complex behavioural pattern which is shaped by cross-scale variables and heuristic rules. This article captures the complexity and dynamic behaviour of migration in Tehri Garhwal district of Uttarakhand using agent-based modelling (ABM). Scenarios considering different starting points were developed to understand variables influencing migration. Migration is governed not only by intrinsic factors, but also by extrinsic influences. Exploratory ABM techniques were used to validate the hypothesis assumed to explain migration behaviour in the study area. The results show that migration cannot be steered with policies focused only on economic perspectives.